(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
In this research the lineaments of the Kafanchan area in North-central Nigeria were investigated in order to explore the mineralization zones of the area. Aeromagnetic data over Kafanchan and environs within the Younger Granite Province, in the North-Central Nigeria were collated and analyzed. The aeromagnetic map of the area was interpreted both qualitatively and quantitatively so as to identify the nature of the magnetic sources and the trends direction in the study area. The trend of the Total Magnetic Intensity (TMI) map is predominantly in NE-SW. The First Vertical Derivative (FVD) Lineaments Map was also correlated with LADSAT lineaments map and both maps agreed in most areas. The study area is characterized by predominant magnetic lineament trend in NE-SW direction and subordinate E-W direction. The result also shows that the most significant structural trends affecting the distribution of these magnetic anomalies in the study area is in NE-SW direction. The TMI map indicates that there are three major mineralization zones in the study area. The high magnetization contrast in the NE and SE parts of the study area correlates with the migmatite-gneiss, biotite-granites, granites and basalts which are associated with high magnetic contrasts. Also, the high magnetization contrast in the NW part of the area correlates with basalt and the biotite-granite. However, the predominant low magnetization contrast observed in the western half does not correlate with the basic igneous rock